Different spraying techniques on the deposit of drops in wheat culture - Christovam, Rafael de Souza [UNESP]; Raetano, Carlos Gilberto [UNESP]; Inacio Leite, Leonardo Aparecido; Prado, Evandro Pereira [UNESP]; Ferreira do Amaral Dal Pogetto, Mario Henrique (Univ Estadual Mato Grosso Sul, 2018)
Wheat (Triticum aestivum L.) has important importance in the world, with the appearance of diseases, there is also researching to seek the best efficiency in the control of these pathogens. To obtain better efficiency results in the curative application of fungicides, the present work aimed to evaluate spray techniques on the deposit of droplets on the leaves of the culture. Two experiments were carried out in the experimental area of FCA/UNESP - Campus de Botucatu, being divided into two areas: agriculture area and gravel area. Two experiments were performed in the 3 x 2 factorial scheme with four replicates in Experiment I: three air levels (0; 15; 29 km h(-1)), two spray volumes (100 L ha(-1) and 200 L ha(-1)). In Experiment II, there were three levels of air (0; 15; 29 km h(-1)), and two different angles of inclination of the spray tips with respect to culture (0 degrees and 30 degrees). In the second visible node stages with 53 days after sowing (DAS) and complete rubber production 67 DAS were sprayed with triazole fungicide (tebuconazole). In Experiment I, in the application to the 53 DAS, the treatment with 200 L ha(-1) with 29 km h(-1) was more efficient, for Experiment II the best result was obtained in the 67 DAS with angle of 30 degrees and wind of 15 km h(-1). Based on the study we can obtain better ways of curative control of the pathogens that may come to install in the crop.
Keywords: application technology; air Assistance; spray angle